Marine Conservation Outcomes are More Likely when Fishers Participate as Citizen Scientists: Case Studies from the Mexican Mesoamerican Reef - Fulton, Stuart; Caamal-Madrigal, Jacobo; Aguilar-Perera, Alfonso; Bourillón, Luis; Heyman, William D. (Citizen Science: Theory and Practice, 2018)
Small-scale fishers on Caribbean coral reefs have exploited fish spawn ing aggregations (FSAs) for generations, but intense fishing has led t o the loss of traditional aggregation sites. In many areas, the tradit ional ecological knowledge (TEK) of fishers has contributed greatly to the characterization of spawning aggregations and implementation of l ocal conservation initiatives. TEK has identified more than 40 potenti al FSA sites along the coast of the Mexican Mesoamerican Reef. These s ites have been characterised and scientifically validated, in some cas es with traditional western science and in others, with a participator y citizen-science approach. The objective of this work is to compare t he science and conservation outcomes at these FSA sites. We report tha t those FSA sites where scientific surveys were conducted without comm unity participation remain unprotected. By contrast, the FSAs where lo cal fishers were engaged in characterization and subsequent monitoring are now protected at the behest of the fishers themselves. Conservati on initiatives to protect FSAs can be more effective through a combina tion of TEK, western science, and participatory citizen science involv ing local fishers.
Keywords: Citizen science; Fishers; Spawning Aggregation; Traditional Ecological Knowledge